THE ASSESSMENT OF NATIONAL ROAD SURFACE CONDITIONS ANALYSIS BASED ON THE INTERNATIONAL ROUGHNESS INDEX (IRI) METHOD USING ROADBUMP APPLICATION - Tambunan, Franzsio Gratio; Mukti, Elsa Tri; Kadarini, Siti Nurlaily (Jurnal Teknik Sipil, 2023)
Roads are infrastructure that has a vital role for the community in supporting social and economic activities. Therefore, appropriate handling information is needed for road maintenance and improvement to be on target. One of the methods used is the International Roughness Index (IRI) method with the help of the Road bump application. The purpose of this study is to analyze and recommend handling road surface conditions, as well as to test the validity of the Road bump application with a Laser Profilometer. This research was conducted on the 10 KM section of Trans Kalimantan Road. Comparative data is obtained from secondary data issued by BPJN in 2021 using the Laser Profilometer tool. This study found that the condition of the Trans Kalimantan Road was 80% in the excellent category, 18% in the moderate category, and 2% in the slightly damaged category, and had similarities with the BPJN IRI value of 95%. Road bump also tends to the IRI value to be greater than the BPJN IRI value. Based on the results of this study, the Road bump application can be used as an alternative tool for measuring road surface conditions using the International Roughness Index (IRI) method.